The difference in mercury content in fish Barbodes schiiwanenfeldi and Osteochillus hasselti in Geumpang river of Geumpang district and Mane district, Pidie regency - Hedriansyah Hedriansyah; Khairil Khairil; M Ali S (Jurnal Edubio Tropika, 2018)
Research on Differences in Mercury Content in Barbodes schiiwanenfeldi and Osteochillus hasselti in Geumpang River, Geumpang Subdistrict and Mane Subdistrict Pidie Regency was conducted on October 11, 2016 to November 1, 2016. The objectives of the study were to analyze differences in mercury content in muscle tissue of Barbodes schiiwanenfeldi and Osteochillus hasselti that lives in the Geumpang River of Pidie Regency. The method used in mercury analysis is Atomic Absorption Spectrophotometry (AAS). The results showed the average of total mercury content in Barbodes schiiwanenfeldi muscle tissue taken from Geumpang River at three observation stations was 0.0022 ppm, and the average of total mercury content in muscle tissue of Barbodes schiiwanenfeldi was 0.0007 ppm. The conclusion of this research is the average of mercury content in muscle tissue of Barbodes schiiwanenfeldi and Osteochillus hasselti fishes which were taken from Geumpang River are still on the recommended limit and there are differences of mercury content in the muscle tissue of Barbodes schiiwanenfeldi and Osteochillus hasselti in the area of Geumpang River of Pidie Regency.Keywords: Barbodes schiiwanenfeldi, Osteochillus hasselti, Geumpang River and Mercury.